That was the church that was: how the Church of England lost the English people - Brown, Andrew (Bloomsbury, 2016)
The Church of England still seemed an essential part of Englishness, and even of the British state, when Mrs Thatcher was elected in 1979. The decades which followed saw a seismic shift in the foundations of the C of E, leading to the loss of more than half its members and much of its influence. In England today 'religion' has become a toxic brand, and Anglicanism something done by other people. How did this happen? Is there any way back? This 'relentlessly honest' and surprisingly entertaining book tells the dramatic and contentious story of the disappearance of the Church of England from the centre of public life. The authors - religious correspondent Andrew Brown and academic Linda Woodhead - watched this closely, one from the inside and one from the outside. This book shows what happened and explains why